Mengelola Pendidikan Toleransi Antar Agama Bagi Penutur Asing di Salatiga - Steaven Octavianus; Iskak Sugiyarto; Teguh Parluhutan (Religi: Jurnal Studi Agama-agama, 2021)
Indonesia is a country which has various different tribes and beliefs in its society. Those various tribes, culture and beliefs are spread in all areas of Indonesia. This uniqueness can also be found in Salatiga, a city that is known as mini Indonesia, for its diversities. In 2015 up to 2017, Salatiga got a predicate as one of the most tolerance city in Indonesia based on “Setara Institute” report. The report and predicate are about freedom of religious life in society. This predicate was seen based on local citizen point of view. How if this predicate was portrayed from foreigner citizen’s point of view, considering that there are quite a lot of foreign citizens also in Salatiga.  Based on this phenomenon this research is aimed to find out how foreign citizen portrays the life of religious tolerance in Salatiga. This research uses qualitative approach with descriptive analysis to analyse the data. This research is classified as a case study since it describes the portrayal of religion’s tolerance point of view in one region, in this case is Salatiga. For data collection this research uses semi-structured and in-depth interview method. The interview was conducted in Salatiga with eight foreign citizens as research subject. The result of this study shows that the foreign citizen said that there are respects between religions in Salatiga. However some foreign citizens feel the unfair advantages between major and minor religion. They could not differentiate whether “the unfair advantage” is merely a custom or it is indeed intolerant act. Although they stated that they can receive some of the acts as a local custom, but they need hard effort to state it as a tolerance between religions in Salatiga. Therefore it is an important thing to manage tolerance education of Indonesia for foreign speaker